Discourse specificity of Pedagogy in France. Cartography of a discourse (Praxis Educativa, 2012)
This article is the result of a research about the life and work of the French educator Philippe Meirieu and it tries to show some discourse aspects of pedagogy in France and its relationship with the sciences of education. Pudgy is not the science of education as it appears in other conceptual regions or pedagogic traditions (German or English). Science of education in France appears institutionalized in 1967 and since that date pedagogy inhabits in its bosom as a concept rather than as a disciplinary space. With the aim of understanding the complex discourse of pedagogy we have consulted magazines, books, papers and some doctoral theses in science of education. Among the most important magazines in our field of reference we can mention The French Magazine of Pedagogy (Revue Francaise de Pédagogie), Magazine of Science of Education for the New Era (Revue de Sciencies de l’Education Pour la Nouvelle Era), the Pedagogy Notebooks (Cahiers de Pédagogie), the Magazine Knowledge’s (Revue Savoirs). These magazines appeared on the French university stage some years after the birth of the science of education. As Pedagogy appears as a given concept, it seems that this question is neither the spring nor the interest of the theorists or practicals or experts; it has each day less place in the science of education debates.
Keywords: pedagogy; sciences of education; concept; pedagogical movements